Exploring the factors leading to the failure of millennial entrepreneurs: Challenges in green business - Basmantra, Ida Nyoman; Apsari, Ida Ayu Karina Widya; Gama, Adie Wahyudi Oktavia; Baykal, Elif; Gorda, A.A.A. Ngurah Sri Rahayu (My University, 2024)
In the 21st century, the global economy has experienced a surprising shift, marked by an increasing focus on sustainability. Millennial entrepreneurs have acknowledged the necessity of addressing social and environmental issues and have responded to this changing landscape by embracing green business initiatives. Nevertheless, these entrepreneurs confront substantial challenges stemming from external risks associated with green enterprises. To investigate these challenges, this research employed a qualitative approach, involving semi-structured interviews that combined both organized and unstructured elements to comprehensively explore the subject. The study identifies eight pivotal factors that hinder the success of green businesses led by millennial entrepreneurs. These factors encompass the absence of clear industry policies for green enterprises, a deficiency in technical knowledge related to green practices, a short-term investment mindset resulting in limited financial support, negative evaluations from experts and within the realm of social media, a lack of external pressures promoting sustainability, unfavorable shifts in the external business environment, constraints in aligning business capabilities with sustainability objectives, and flawed business models. Furthermore, researchers have recognized that the inherent characteristics of millennial entrepreneurs also contribute to shaping these factors. The findings highlight the critical influence of these eight factors on the challenges encountered by green businesses, shedding light on how millennial attributes affect the ultimate success or failure of such ventures.
Keywords: Challenges; Failure Factor; Green Business; Millennial Entrepreneurship